2011
DOI: 10.1088/0957-4484/22/41/415703
|View full text |Cite
|
Sign up to set email alerts
|

Excellent dispersion of MWCNTs in PEO polymer achieved through a simple and potentially cost-effective evaporation casting

Abstract: A simple, reliable and potentially cost-effective composite film casting procedure is presented using the evaporation of solvent (water) from a dilute mixture of multiwalled carbon nanotubes (MWCNTs) and polyethylene oxide (PEO) polymer. It is found that the fabrication method develops excellent dispersion of MWCNTs in PEO confirmed by morphology observations, final crystallinity of polymer (amorphous) and a lower percolation threshold (closer to theoretical value) as well as higher electrical conductivity. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…There are several opposing observations reported in literature on PEO crystallization in the presence of MWNTs. Park et al found that MWNTs hinder PEO crystallization, and above 10 % nanotube loading the SAXS pattern does not show any lamellar reflection from PEO crystals [40]. Similarly, Abraham and coworkers reported $10 % decrease in PEO % crystallinity at $3-4 % MWNTs loading [122].…”
Section: Crystallization Of Peo In the Presence Of Carbon Nanotubesmentioning
confidence: 94%
See 3 more Smart Citations
“…There are several opposing observations reported in literature on PEO crystallization in the presence of MWNTs. Park et al found that MWNTs hinder PEO crystallization, and above 10 % nanotube loading the SAXS pattern does not show any lamellar reflection from PEO crystals [40]. Similarly, Abraham and coworkers reported $10 % decrease in PEO % crystallinity at $3-4 % MWNTs loading [122].…”
Section: Crystallization Of Peo In the Presence Of Carbon Nanotubesmentioning
confidence: 94%
“…This indicates that beyond the percolation threshold, cluster effect is more pronounced than the individual nanoparticles' dispersion state. Park et al observed a percolation threshold between 1.0 and 2.0 vol% for MWNTs in PEO and summarized the percolation threshold for carbon nanotubes-PEO nanocomposites reported by different research groups [40]. Finally, while many of the previous studies have shown that electrical and geometrical percolations are coincident [53,54] or that the value for the electrical percolation threshold is somewhat greater than the corresponding geometrical percolation [55,56], it is anticipated [57] and observed for multiwalled carbon nanotube-polymer composites that the connectivity (i.e., electrical) percolation precedes the rigidity (i.e., geometrical) percolation [58].…”
Section: Characterization Of Dispersionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is implemented by mixing the nanotubes with water soluble polymer and the evaporation process is either using low temperature ovens or simply by letting it dry at room temperature . Recently, Park et al demonstrated multiwalled carbon nanotubes—polyethylene oxide (PEO) composite film using evaporation technique that makes use of the low melting temperature of PEO.…”
Section: Introductionmentioning
confidence: 99%